2010
DOI: 10.1111/j.1523-1739.2010.01606.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Value of the Umbrella-Species Concept for Conservation Planning with Meta-Analysis

Abstract: The umbrella-species concept, which suggests that conservation strategies designed for one species may benefit co-occurring species, has been promoted as a framework for conservation planning. Nevertheless, there has been considerable variation in the outcome of empirical tests of this concept that has led researchers to question its value, so we used data from 15 published studies in a meta-analysis to evaluate whether conservation of putative umbrella species also conserves co-occurring species. We tested th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
128
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(135 citation statements)
references
References 39 publications
5
128
0
2
Order By: Relevance
“…In addition, since they are considered to be sentinel species (Bossart, 2011) their status can inform on the status of whole ecosystem. Indeed marine megafauna could be considered as umbrella species (Zacharias and Roff, 2001;Branton and Richardson, 2011) because their effective conservation should incorporate the conservation of a suite of lower trophic level species and associated ecosystem services. Moreover, top predators can play a key role in maintaining biodiversity patterns by either top-down control or behaviorally mediated mechanisms (Heithaus et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, since they are considered to be sentinel species (Bossart, 2011) their status can inform on the status of whole ecosystem. Indeed marine megafauna could be considered as umbrella species (Zacharias and Roff, 2001;Branton and Richardson, 2011) because their effective conservation should incorporate the conservation of a suite of lower trophic level species and associated ecosystem services. Moreover, top predators can play a key role in maintaining biodiversity patterns by either top-down control or behaviorally mediated mechanisms (Heithaus et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Umbrella species are proposed to serve as conservation umbrellas for a number of other species with shared habitat or management requirements (Roberge & Angelstam 2004b;Branton & Richardson 2011). Related hereto, the Focal species concept is basically a multispecies umbrella species approach, where a set of selected species are proposed to have specific life history characteristics that are expected to confer protection to other species that are facing similar threats if addressed properly in conservation planning (Nicholson et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, several studies have found that flagship species conservation programmes may have limited effectiveness in conserving other species [14,15], and that species such as large predators (which are often flagship species [6]) may have relatively low utility as 'umbrella' species for conserving biodiversity in general [16]. However, such studies have generally examined habitat overlaps rather than synergistic benefits of conservation actions that may be shared among species.…”
Section: Introductionmentioning
confidence: 99%